2010
DOI: 10.1007/s11284-009-0686-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to a limiting environment: the phosphorus content of terrestrial cave arthropods

Abstract: Stoichiometric imbalances (mismatches between elemental ratios of consumers and their food) are expected to be especially important in detritus-based systems because poor resource quality may impose severe growth constraints. Such imbalances have been highlighted in producer-based food webs and detritusbased aquatic systems, but similar investigations of detritus-based terrestrial ecosystems are absent. Cave animals are dependent on detrital subsidies from the surface and display adaptations to caves (e.g., de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Previous studies have shown that the P content of carnivores is higher (Cross et al, ; González et al, ; Lemoine et al, ; Wiesenborn, ) or the same (Martinson et al, ; Schneider et al, ) as that of detritivores. In this study, trophic group differences in P content depended on site, suggesting that some of the divergent results between previous studies reflect local conditions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies have shown that the P content of carnivores is higher (Cross et al, ; González et al, ; Lemoine et al, ; Wiesenborn, ) or the same (Martinson et al, ; Schneider et al, ) as that of detritivores. In this study, trophic group differences in P content depended on site, suggesting that some of the divergent results between previous studies reflect local conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, carnivores have access to higher quality resources and may therefore rely more heavily on higher nutrient materials to build their bodies (Fagan et al, 2002;González et al, 2011;Lemoine et al, 2014). Nevertheless, the generalization of an increase in nutrient-rich biomass with increasing trophic position has been recently disputed for arthropods, in particular regarding P content and N:P (Lemoine et al, 2014;Schneider, Kay, & Fagan, 2010;Woods et al, 2004). This suggests that the role of trophic guild in determining the elemental content of arthropods, and perhaps invertebrates in general, may depend on the identity of species in the community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), several elements of fundamental importance to arthropod metabolism became limiting (phosphorus and carbon in particular; Medici and Taylor, 1966;Vigh and Dendinger, 1982;Denno and Fagan, 2003;Capinera, 2008;Schneider et al, 2010). However, no corresponding effects of litter addition were observed in terms of arthropod absolute and relative abundances, which suggests that the above elements were in sufficient supply in most control plots, at least in terms of their effects on soil arthropods.…”
Section: Relation Of Arthropod Responses To Soil Characteristicsmentioning
confidence: 99%
“…With higher P availability in the soil, more large-bodied invertebrates were found [19]. Schneider et al [25] compared stoichiometric data of slow-growing cave arthropods (Collembola, Coleoptera, Orthoptera, millipedes, arachnids) to their surfacedwelling counterparts and found lower P contents in their body mass. Hamb€ ack et al [11] compared stoichiometry of Diptera diets and bodies and found that Diptera body N did not directly increase with diet quality.…”
Section: Introductionmentioning
confidence: 99%